SOIL FOUNDATION IMPROVEMENT WITH TIRE-USED TO REDUCE SETTLEMENT OF SHALLOW FOUNDATION EMBEDDED ON SATURATED DEPOK CLAY - PUTERA AGUNG M.A; Sony Pramusandi; IMAM Hariadi Sasongko (Jurnal Poli-Teknologi, 2014)
ABSTRACT One of soil foundation improvement methods to anticipate the problem of settlement is to use tire-used (pneusol). This is a preliminary study and aims to determine the reduction of vertical displacement or settlement on saturated clay reinforced with tire-used. Tire-used material generally has a density of between 8 and 10 kn/m3 and is usually classified as a material lightweight tire. Laboratory model test used 4 (four) models, model with and without tire-used and some variations of foundation model size (rollag). Ratio of the diameter of tire-used and rollag size is 0.60. Results are compared with the data obtained by plaxis program. Analysis of the plaxis program assumed that plane strain triangle element type; 6 (six) nodes element; mohr – coulomb criteria; and soil foundation in undrained condition. Results of the experimental model at laboratory works show that the tire-used can reduce the settlement of soil foundation up to 20% at maximum normal stress. However, the value of settlement obtained by experimental model at laboratory works could not be compared with the plaxis program results. Keywords : tire used, hallow foundation, bearing capacity,settlement